Narrow-breadth double-layer solid-liquid composite material based on molten aluminum, preparation method and application
By using spray drying on the bonding surface of the strip, solid phase particles are formed and combined with liquid aluminum through casting and rolling process, the problem of insufficient interface bonding strength of solid-liquid composite metal materials is solved, and higher mechanical properties and thermal conductivity are achieved.
Patent Information
- Application Number
- CN202510312897.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The interface bonding strength of existing solid-liquid composite metal materials is insufficient, resulting in the mechanical properties not meeting the standards, and problems such as increasing viscosity of liquid metals and oxidation of solid phase particles are prone to occur during the casting and rolling process.
The spray drying method is used to form solid phase particles on the bonding surface of the strip, and the liquid aluminum is combined with the solid phase particles through the casting and rolling process to form a narrow-form double-layer solid-liquid composite material. This method avoids the direct introduction of solid phase particles into liquid aluminum, reduces shrinkage and shrinkage, and promotes atomic diffusion at the solid-liquid interface.
The interface bonding strength and thermal conductivity of solid-liquid composite materials are improved, the oxidation of solid-phase particles and the formation of intermetallic compounds are reduced, and the mechanical properties and production efficiency of the material are enhanced.
Smart Images

Figure CN119794308A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of metal composite materials, and in particular to a narrow-width double-layer solid-liquid composite material based on liquid aluminum, a preparation method and application thereof. Background Art
[0002] Solid-liquid composite metal materials specifically refer to a method of combining solid metal and liquid metal on a rolling mill through a liquid-solid composite method (also known as a casting and rolling method). This method combines the casting method and the rolling method, that is, it has the diffusion ability of the liquid phase at high temperature and the pressure of rolling, and can achieve a higher composite strength. At the same time, it is suitable for continuous production, with the characteristics of high efficiency and low cost. However, there are still some problems in this process, which makes it difficult to promote and apply it on a large scale. When using different types of liquid metals and solid metals, if the compatibility of the two is poor, the interface bonding strength of the formed solid-liquid composite metal material is too poor, resulting in the mechanical properties of the composite metal material failing to meet the requirements. By adding solid particles to the liquid phase, the solid particles distributed at the solid-liquid interface during the casting and rolling process can form a mechanical locking structure, thereby improving the interface bonding strength. However, this method will also lead to other problems, such as increasing the viscosity of the liquid metal and affecting the fluidity, the solid particles will form an intermetallic composite with the liquid metal, and the melting point of the solid particles needs to be greater than the temperature of the liquid metal.
[0003] Therefore, it is necessary to propose a narrow-width double-layer solid-liquid composite material based on liquid aluminum, a preparation method and an application. Summary of the invention
[0004] Based on this, a narrow-width double-layer solid-liquid composite material based on liquid aluminum, a preparation method and an application are provided.
[0005] The first aspect of the present invention provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum, comprising the following steps: roughening the bonding surface of the plastic processing material, forming solid phase particles on the bonding surface of the plastic processing material by spray drying, wherein the solid phase particles contain a metal with a melting point not higher than 650°C, preparing liquid aluminum, and continuously casting the liquid aluminum on the bonding surface of the strip by a casting and rolling process, wherein the solid phase particles and the liquid aluminum move with the plastic processing material to pass through a rolling roller and are post-processed to form the narrow-width double-layer solid-liquid composite material, wherein the roughness of the bonding surface is 1-5μm, and the average particle size of the solid phase particles is 1-5μm.
[0006] The above scheme forms solid phase particles on the strip bonding surface by spray drying and embeds them into the pores formed by roughening the bonding surface, avoiding the influence of directly introducing solid phase particles into liquid aluminum on the fluidity of liquid aluminum, and can reduce shrinkage cavities and shrinkage in the aluminum layer of the composite material. At the same time, during the casting and rolling process, the particles can be plastically deformed with the liquid aluminum and the strip bonding surface under the rolling pressure to form a mechanical interlocking structure, thereby improving the interface bonding effect; the solid phase particles contain metals with a melting point lower than 650°C, and during the casting and rolling process, the solid phase particles soften or partially dissolve, thereby promoting atomic diffusion at the solid-liquid interface, and further achieving a tighter metallurgical bonding; compared with the method of directly adding solid phase particles to liquid aluminum, on the one hand, it can prevent the solid phase particles from being oxidized at high temperature for a long time to cause oxide inclusions, and on the other hand, it can reduce the reaction between the solid phase particles and liquid aluminum to form intermetallic compounds. At the same time, the spray drying method can make the solid phase particles evenly distributed on the surface of the strip, solving the problem of uneven distribution of solid phase particles and further improving the mechanical properties of the composite material.
[0007] Furthermore, the solid phase particles contain aluminum and at least one of copper, nickel, iron and titanium. A more complex reinforcement phase can be formed by combining multiple elements to improve the interface bonding effect.
[0008] Furthermore, the solid phase particles contain at least one metal component of the plastic processing material and aluminum. The use of the above combination can improve the compatibility of the solid phase particles with the liquid aluminum and the strip, thereby promoting interface atomic diffusion to improve the interface bonding effect.
[0009] Furthermore, the roughness of the bonding surface is 1 μm, and the average particle size of the solid phase particles is 1 μm.
[0010] Furthermore, when preparing the liquid aluminum, 0.1-0.3% by mass of aluminum titanium boron wire is added as a refiner. The refiner can promote crystal refinement, reduce casting defects such as shrinkage cavities and shrinkage, and improve the density and mechanical properties of the aluminum layer. Elements such as titanium and boron can inhibit the generation of harmful phases and further promote interface bonding.
[0011] Furthermore, the continuous casting speed is 500 mm / min-2000 mm / min. High-speed continuous casting can improve production efficiency, but it is also necessary to avoid the continuous casting speed being too low, which may cause uneven solidification of liquid aluminum and affect the interface bonding effect.
[0012] Furthermore, the post-treatment includes an annealing step, and the parameters of the annealing step are: 150-300°C, 0.5-12h. The annealing step can eliminate the stress generated during the casting and rolling process and promote interface atomic diffusion and metallurgical bonding.
[0013] Furthermore, the plastic processing material contains at least one element selected from the group consisting of copper, aluminum, steel, nickel and titanium, and may be replaced with a combination of other elements depending on the usage scenario.
[0014] The second aspect of the present invention provides a narrow width double-layer solid-liquid composite material based on liquid aluminum, which is prepared using the above preparation method. The narrow width double-layer solid-liquid composite material has a thickness of 2-12 mm and a width of ≤200 mm. Composite materials with a width of ≤200 mm are generally referred to as narrow width materials.
[0015] The composite material obtained by the preparation method has better interface bonding strength and thermal conductivity.
[0016] The third aspect of the present invention provides an application of the above-mentioned narrow-width double-layer solid-liquid composite material, which applies the narrow-width double-layer solid-liquid composite material to the fields of new energy, electronic information, intelligent equipment, aerospace, medical health or military industry.
[0017] Specifically, the new energy field includes new energy vehicles, batteries, electrochemical energy storage systems, photovoltaic power generation equipment, wind power equipment, and more specifically battery poles, battery casings, battery covers, heat sinks, copper-aluminum bus bars, and power pipes; the electronic information field includes 3C electronics, semiconductor components and production equipment, and communication systems; the intelligent equipment field includes robots, intelligent transportation vehicles, and computer systems; the aerospace field includes drones, helicopters, and satellite systems; the medical and health field includes medical equipment and instruments.
[0018] It can be understood that the above-mentioned composite materials are applied to the above-mentioned fields to meet the requirements of these fields for high strength, corrosion resistance and high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a metallographic image of the composite material of Example 1.
[0020] Figure 2 This is the metallographic image of the composite material of Comparative Example 1. DETAILED DESCRIPTION
[0021] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0022] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0024] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0025] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0026] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0027] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0028] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0029] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.
[0030] Example 1: A method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum.
[0031] Aluminum liquid formula: by mass fraction, it contains 1.2% magnesium, 0.6% silicon, 0.2% copper, 0.15% manganese, 0.2% zinc, 0.05% chromium, and 0.5% iron.
[0032] Solid phase particle composition: by mass fraction, it contains 10% copper and 90% aluminum.
[0033] S1: Melting: heating the aluminum ingot to 700-750℃ for melting; S2: Degassing and deslagging: add 0.3% (mass fraction) refining agent (HGJ-2 type sodium-free refining agent), blow in argon gas, and stir to degas and deslagging; S3: Add different metal elements according to the formula of aluminum liquid; S4: Standing: Maintain the aluminum liquid at 700° C. for 10 minutes (in some embodiments, the temperature can be selected between 700-750° C., and the time can be selected between 10-30 minutes); S5: Grain refinement: Add 0.3% (mass fraction) aluminum titanium boron wire to the aluminum liquid for grain refinement; S6: Copper strip pretreatment: The bonding surface of the copper strip (the side compounded with the aluminum liquid) is mechanically roughened to make its surface roughness 3μm. Solid phase particles with an average particle size of 5μm are formed on the bonding surface by spray drying, and the spraying density is 0.1g / mm 3 ; S7: Casting and rolling composite: 670℃ aluminum liquid is continuously cast on a copper strip (25℃) through a casting system, and crystallized and composited at the casting roll. The continuous casting speed is 2000mm / min, the composite width is 100mm (in other embodiments, it can be selected between 10-200mm as needed), the composite thickness is 10mm (in other embodiments, it can be selected between 2-12mm as needed), the rolling pressure is 800000N (in other embodiments, it can be selected between 50000N-1000000N as needed), the roll temperature is 150℃ (in other embodiments, it can be selected between 150-300℃ as needed), the rolling tension is 5000N (in other embodiments, it can be selected between 5000-10000N as needed), and the roll is cooled by water; S8: Initial cutting: Cut off the excess aluminum on both sides (it can be returned to the furnace for smelting after cleaning and drying); S9: Finish rolling: Finish rolling is performed to obtain a composite material with a thickness of 5 mm, and the finishing temperature is 200°C; S10: Finishing cutting: cutting off the overflowed materials on both sides of the finishing rolling for recycling; S11 annealing: annealing temperature 150°C, holding time 12 hours; S12: Grinding: Grinding is performed to remove the oxide scale on the upper and lower surfaces of the composite material, and finally a narrow-width double-layer solid-liquid composite material is obtained.
[0034] Example 2: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the roughness of the strip bonding surface is 1 μm, and the average particle size of the solid phase particles is 1 μm.
[0035] Example 3: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the addition amount of aluminum-titanium-boron wire is 0.1%, the thickness of the composite material during casting and rolling is 12 mm, and the thickness of the composite material after fine rolling is 6 mm.
[0036] Example 4: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the parameters of the annealing step are 300° C. and 0.5 h.
[0037] Example 5: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the strip is changed to a nickel strip, and the composition of the solid phase particles is an aluminum-nickel mixture (in terms of mass fraction, the ratio of aluminum to nickel is 9 / 1).
[0038] Example 6: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the density of the sprayed solid phase particles is 0.3 g / mm 3 .
[0039] Example 7: This example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the component of the solid phase particles is pure aluminum.
[0040] Comparative Example 1: This comparative example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that in step S6, solid phase particles are not formed on the bonding surface by spray drying.
[0041] Comparative Example 2: This comparative example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that in step S5, solid phase particles with a mass fraction of 3% are additionally added, and the average particle size of the solid phase particles is 5μm. In step S6, solid phase particles are not formed on the bonding surface by spray drying, that is: S5: Grain refinement: 0.3% (mass fraction) aluminum titanium boron wire is added to the aluminum liquid for grain refinement, and 3% of solid phase particles are added at the same time, and the average particle size of the solid phase particles is 5μm; S6: Copper strip pretreatment: The bonding surface of the copper strip (the side compounded with the aluminum liquid) is mechanically roughened so that the surface roughness is 3μm.
[0042] Comparative Example 3: This comparative example provides a method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum. The difference from Example 1 is that the roughness of the strip bonding surface is 0.5 μm, and the average particle size of the solid phase particles is 5 μm.
[0043] The interface bonding force and thermal conductivity of the heat sinks of Examples 1-7 and Comparative Examples 1-3 were tested. Test method: interface bonding force (tested by referring to the peeling method in GJB 446-1988, the peeling strength is the interface bonding force of this embodiment), thermal conductivity of the copper-aluminum composite metal plate (measurement of the thermal conductivity of the copper-aluminum composite metal plate by ISO8301 AMD 1-2010). The test results are shown in Table 1: Table 1: Test results of interface bonding force and thermal conductivity of embodiments and comparative examples.
[0044]
[0045] According to the data in Table 1, the interface bonding force and thermal conductivity of Examples 1-4 and 6 are better than those of Comparative Examples 1-3. This is because the above scheme forms solid-phase particles on the strip bonding surface by spray drying, avoiding the influence of directly introducing solid-phase particles into liquid aluminum on the fluidity of liquid aluminum, reducing shrinkage cavities and shrinkage in the aluminum layer of the composite material, and forming a mechanical interlocking structure with the liquid aluminum and the strip bonding surface during the casting and rolling process to improve the interface bonding effect; the melting point of the solid-phase particles is lower than the melting point of liquid aluminum, and the solid-phase particles soften or dissolve during the casting and rolling process, thereby promoting atomic diffusion at the solid-liquid interface and further achieving a tighter metallurgical bonding; compared with the method of directly adding solid-phase particles to liquid aluminum, on the one hand, it can prevent the solid-phase particles from being oxidized at high temperature for a long time to cause oxide inclusions, on the one hand, it can reduce the reaction between the solid-phase particles and the liquid aluminum to form intermetallic compounds, and on the other hand, the solid-phase particles can be evenly distributed on the surface of the strip by spray drying, solving the problem of uneven distribution of solid-phase particles and further improving the mechanical properties of the composite material. Comparative Example 1 lacks the mechanical intercalation of solid phase particles and the effect of promoting atomic diffusion, resulting in reduced interfacial bonding strength, such as Figure 1-2 As shown, comparative example 1 produces more interface defects, resulting in a decrease in thermal conductivity, while the interface of example 1 is tightly bonded, with better thermal conductivity and interface bonding strength. Comparative example 2 adds solid phase particles during the preparation of aluminum liquid, and the aluminum of the solid phase particles melts in the aluminum liquid. In fact, the solid phase particles are equivalent to copper particles, and some copper particles are deposited at the bottom with a certain mechanical interlocking effect, but they cannot achieve the effect of promoting atomic diffusion, and will affect the fluidity of aluminum liquid, produce more interface defects, and lead to a decrease in thermal conductivity. The particle size of the solid phase particles in comparative example 3 is much larger than the roughness of the bonding surface, and the solid phase particles are difficult to embed into the bonding surface. The solid phase particles cannot be evenly distributed, so it is difficult to exert their physical interlocking effect, and the quality of the solid-liquid interface will be deteriorated.
[0046] Example 2 uses the preferred roughness and average particle size to achieve better physical interlocking and form a denser bonding layer, thereby having higher interface bonding force and thermal conductivity. Example 5 uses nickel strips and can also obtain better thermal conductivity and interface bonding strength, indicating that this solution can be applied to other strips.
[0047] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a narrow-width double-layer solid-liquid composite material based on liquid aluminum, characterized in that: The method comprises the following steps: roughening the bonding surface of the plastic processing material, forming solid phase particles on the bonding surface by spray drying, wherein the solid phase particles contain a metal with a melting point not higher than 650°C, preparing the liquid aluminum, and continuously casting the liquid aluminum on the bonding surface by a casting and rolling process, wherein the solid phase particles and the liquid aluminum move with the plastic processing material to pass through a roller and are post-processed to form the narrow width double-layer solid-liquid composite material, wherein after the roughening treatment, the roughness of the bonding surface is 1-5 μm, and the average particle size of the solid phase particles is 1-5 μm.
2. The preparation method according to claim 1, characterized in that: The solid phase particles include aluminum and at least one of copper, nickel, iron, and titanium.
3. The preparation method according to claim 1, characterized in that: The solid phase particles contain at least one metal component of the plastically worked material and aluminum.
4. The preparation method according to claim 1, characterized in that: The plastically processed material comprises at least one of a profile, a plate or a strip.
5. The preparation method according to claim 1, characterized in that: The roughness of the bonding surface is 1 μm, and the average particle size of the solid phase particles is 1 μm.
6. The preparation method according to claim 1, characterized in that: When preparing the liquid aluminum, 0.1-0.3% by mass of aluminum titanium boron wire is added as a refining agent.
7. The preparation method according to claim 1, characterized in that: The post-treatment comprises an annealing step, and the parameters of the annealing step are: 150-300° C., 0.5-12 h.
8. The preparation method according to claim 1, characterized in that: The plastic working material contains at least one element of copper, aluminum, steel, nickel and titanium.
9. A narrow-width double-layer solid-liquid composite material based on liquid aluminum, characterized in that: The narrow-width double-layer solid-liquid composite material is prepared by the preparation method described in any one of claims 1 to 8, and the thickness of the narrow-width double-layer solid-liquid composite material is 2-12 mm, and the width is ≤200 mm.
10. An application of the narrow width double-layer solid-liquid composite material as claimed in claim 9, characterized in that: The narrow-width double-layer solid-liquid composite material is applied to the fields of new energy, electronic information, intelligent equipment, aerospace, medical health or military industry.
Citation Information
Patent Citations
Composite coating layer on surface of high-resistant crystallizer or crystallizing roller and manufacturing method thereof
CN102039384A
Asynchronous casting rolling method for preparing superfine crystal copper-aluminum composite sheet strip
CN110340317A
Production of composite body
JP1983025847A
Production of clad steel plate
JP1987259641A
Method of manufacturing composite strips by continuous casting
US4224978A
Cited By
Preparation method of horizontal continuous casting copper-aluminum composite material
CN122352867A